Near-deterministic hybrid generation of arbitrary photonic graph states using a single quantum emitter and linear optics - Hilaire, Paul; Vidro, Leonid; Eisenberg, Hagai S.; Economou, Sophia E. (Quantum, 2023)
Paul Hilaire, Leonid Vidro, Hagai S. Eisenberg, and Sophia E. Economou, Quantum 7, 992 (2023). Since linear-optical two-photon gates are inherently probabilistic, measurement-based implementations are particularly well suited for photonic platforms: a large highly-entangled photonic r…
Publisher: Verein zur Förderung des Open Access Publizierens in den Quantenwissenschaften